Cardiac Magnetic Resonance Imaging Findings in Patients With Antineutrophil Cytoplasmic Antibody–Associated Vasculitides: A Systematic Review - Ioannis Karageorgiou; Unnati Bhatia; Hazem Alakhras; Berk Celik; Alexandra Halalau (ACR Open Rheumatology)
Objective Our objective was to review the available literature on cardiac magnetic resonance imaging (cMRI) findings in patients with antineutrophil cytoplasmic antibody–associated vasculitides (AAV), evaluate its diagnostic utility, and assess its potential as a screening tool. Methods We systematically searched PubMed, Embase, Scopus, and Web of Science from inception to March 29, 2023, following Preferred Reporting Items for Systematic reviews and Meta‐Analyses (PRISMA) 2020 guidelines. English‐language studies involving adult patients diagnosed with AAV—eosinophilic granulomatosis with polyangiitis (EGPA), granulomatosis with polyangiitis (GPA), or microscopic polyangiitis (MPA)—using recognized classification criteria were included. Studies had to report specific cMRI parameters in at least three patients. Three independent reviewers conducted study selection, data extraction, and quality assessment. Results Of 2,251 studies, 30 met the inclusion criteria, encompassing 1,149 patients with AAV (87% with EGPA, 13% with GPA, and 0.3% with MPA). The mean patient age was 52 ± 5 years, with 50.4% being female. The mean left ventricular ejection fraction (LVEF) was 55.6% ± 11.3%, and 29% of patients had an LVEF less than 50%. Myocardial fibrosis, indicated by late gadolinium enhancement (LGE), was present in 49% of patients, with predominantly subendocardial or endocardial (23%), intramyocardial (14%), and subepicardial (10%) patterns. Patients in remission (26%), when compared to those not in remission (74%), exhibited higher proportions of LGE (55% vs 47%) and glucocorticoid use (77% vs 68%), despite similar rates of abnormal electrocardiograms (44% vs 42%). Conclusion This systematic review reveals a high prevalence of myocardial fibrosis detected by cMRI in patients with AAV, even during remission. Significant subclinical cardiac involvement may be missed by conventional diagnostic methods, underscoring the utility of cMRI during routine evaluation.